Efektivitas Ethno-Cinema Education untuk Meningkatkan Green Jobs Awareness pada Generasi Z - Beny Dwi Pratama; Tyas Martika Anggriana; Juwita Finayanti; Asroful Kadafi; Rohman Harianto; Riski Yanuar Ratnawati Kusuma (Universitas Muhammadiyah Metro, 2025)
Global transitions toward a green economy require the younger generation to develop awareness of environmentally friendly occupations, commonly referred to as green job awareness. However, data from the 2023 Agricultural Census indicate that youth interest in the agricultural sector in Madiun Regency remains critically low, with only 1% participation among individuals aged 15–24 years. This condition highlights the urgency of developing educational strategies that align with the characteristics of Generation Z, who are widely recognized as digital natives with strong visual and technological learning preferences. This study aimed to develop and examine the effectiveness of Ethno-Cinema Education media in enhancing green job awareness among Generation Z. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analyze, Design, Development, Implementation, and Evaluation stages. The developed products comprised two educational videos: (1) a documentary video presenting local green job practices in Madiun Regency, and (2) an instructional video explaining the concepts and various types of green job professions. The effectiveness of the developed media was tested using a one-group pretest–posttest design involving 58 senior high school and vocational school students in Madiun Regency. Data were analyzed using a paired-sample t-test. The results revealed a significant difference between pre-test scores (M = 76.71; SD = 9.13) and post-test scores (M = 77.88; SD = 9.31), with a significance value of p = 0.000 (p < 0.05). These findings demonstrate that Ethno-Cinema Education media is effective in increasing students’ awareness of environmentally friendly occupations. This study contributes to the development of innovative career guidance services that integrate cultural values and digital technology in a contextual manner. The findings further suggest that an educational cinema-based approach incorporating local wisdom can serve as an effective strategy for fostering environmentally conscious career awareness among adolescents and Generation Z.